2020
DOI: 10.1515/pthp-2020-0009
|View full text |Cite
|
Sign up to set email alerts
|

Measurement, analysis and prediction of amoxicillin oral dose stability from integrated molecular description approach and accelerated predictive stability (APS)

Abstract: BackgroundStability of low amoxicillin oral dosage form (5 mg) used in reintroduction drug test was not fully documented. Furthermore, the impact of (1) salt moiety of amoxicillin and (2) amoxicillin – excipient interactions upon the antibiotic formulation stability during the storage was not characterized so that the estimation of the pharmaceutical expiration date from shelf-life was uncertain. Thus, the main goal of this study was to estimate the shelf-life of two formulations of amoxicillin, using a semi-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…FTIR spectra of amoxycillin trihydrate showed that the characteristic peak of the drug is present in the peak (12). The infrared spectrum of the Amoxycillin trihydrate showed strong absorption at 1,776 cm −1 , characteristic of the β-lactam ring 28 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…FTIR spectra of amoxycillin trihydrate showed that the characteristic peak of the drug is present in the peak (12). The infrared spectrum of the Amoxycillin trihydrate showed strong absorption at 1,776 cm −1 , characteristic of the β-lactam ring 28 .…”
Section: Resultsmentioning
confidence: 99%
“…The comparison was carried out between 3700 cm -1 and 2400 cm -1 and between 1800 cm -1 and 1000 cm -1 . Alkenyl (>C=C); 3,020-3,100 cm -1 ; and amide (>NH; 1,000-1,250 cm -1 ) Phenolic (-OH; 970-1,250 cm-1 ) and ketone (>C=O; 1,710-1,720 cm -1 ) stretches are the primary functional groupings in charge of certain areas 28,29 . The FTIR data reveals the formation of weak to medium intensity bonds, which may be caused by the development of Vander Waal forces and dipole moments due to the interaction of the drug and excipient.…”
Section: Resultsmentioning
confidence: 99%
“…The infrared spectrum was recorded using an ATR/FT-IR spectrometer (3800-400 cm −1 , 10 cm optical path, 32 scans with spectral resolution of 4 cm −1 , Nicolet ® iS 50 FT-IR spectrometer, Thermo Fisher Scientific). 2,3 The ATR/ FT-IR spectrum obtained was compared to the MIND ATR/FT-IR spectrum module database. Finally, a multi-component deconvolution of the initial spectrum was carried out to identify up to four individual components of the unknown crushed pellets.…”
Section: Methodsmentioning
confidence: 99%
“…The stability-indicating quantitative analytical method was used to study the stability of the compounded formulation. In an emergency context, two methods were applied to assess the stability: a semi-predictive method (based on the Arrhenius equation and the kinetics equations developed during the 20 th century), allowing a very fast assessment, and a prospective method (classical method) as a confirmation of the prediction ( Šesták and Berggren, 1971 , Waterman and Adami, 2005 , Merienne et al, 2020 , Clénet, 2018 ).…”
Section: Introductionmentioning
confidence: 99%